Eyes see what brain knows-a diagnostic hustle-ruptured interstitial pregnancy masqueraded as ovarian simple cyst torsion: a case report - Jain, Dikshita; Gupta, Alka; Shikhanshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ectopic pregnancy accounts for 2-3% of total pregnancies and is one of the common causes of first-trimester bleeding and maternal morbidity and mortality. It occurs when a blastocyst gets implanted outside the uterine cavity, most commonly in the fallopian tubes. It is generally characterized by a triad of a period of amenorrhea, per vaginal bleeding, and pain in the abdomen. Around 2-4% of total ectopic pregnancies are due to implantation at the interstitial part of the fallopian tube. Being supported by nearby myometrium it usually presents late. Because of its location, it can lead to cornual rupture causing complications like torrential bleeding, which can be life-threatening. Here we present a case of a 35-year-old female presenting with acute abdominal pain, no period of amenorrhea and an ovarian cyst mimicked as ovarian cyst torsion which ultimately got diagnosed as ruptured interstitial pregnancy.